Restricted T cell receptor repertoire in CLL-like monoclonal B cell lymphocytosis and early stage CLL. (3rd June 2018) - Blanco, Gonzalo; Vardi, Anna; Puiggros, Anna; Gómez-Llonín, Andrea; Muro, Manuel; Rodríguez-Rivera, María; Stalika, Evangelia; Abella, Eugenia; Gimeno, Eva; López-Sánchez, Manuela; Senín, Alicia; Calvo, Xavier; et al.
ABSTRACT: Analysis of the T cell receptor (TR) repertoire of chronic lymphocytic leukemia-like monoclonal B cell lymphocytosis (CLL-like MBL) and early stage CLL is relevant for understanding the dynamic interaction of expanded B cell clones with bystander T cells. Here we profiled the T cell receptor β chain (TRB) repertoire of the CD4 + and CD8 + T cell fractions from 16 CLL-like MBL and 13 untreated, Binet stage A/Rai stage 0 CLL patients using subcloning analysis followed by Sanger sequencing. The T cell subpopulations of both MBL and early stage CLL harbored restricted TRB gene repertoire, with CD4 + T cell clonal expansions whose frequency followed the numerical increase of clonal B cells. Longitudinal analysis in MBL cases revealed clonal persistence, alluding to persistent antigen stimulation. In addition, the identification of shared clonotypes among different MBL/early stage CLL cases pointed towards selection of the T cell clones by common antigenic elements. T cell clonotypes previously described in viral infections and immune disorders were also detected. Altogether, our findings evidence that antigen-mediated TR restriction occurs early in clonal evolution leading to CLL and may further increase together with B cell clonal expansion, possibly suggesting that the T cell selecting antigens are tumor-related.